2011
DOI: 10.1302/0301-620x.93b6.25849
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent slipped capital femoral epiphysis treated by a modified Dunn osteotomy with surgical hip dislocation

Abstract: Between June 2001 and November 2008 a modified Dunn osteotomy with a surgical hip dislocation was performed in 30 hips in 28 patients with slipped capital femoral epiphysis. Complications and clinical and radiological outcomes after a mean follow-up of 3.8 years (1.0 to 8.5) were documented. Subjective outcome was assessed using the Harris hip score and the Western Ontario and McMaster Universities osteoarthritis index questionnaire. Anatomical or near-anatomical reduction was achieved in all cases. The epiphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
2
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 36 publications
7
71
2
3
Order By: Relevance
“…It is unclear, however, whether revascularization was related to the integrity of the retinacular vessels or if it may have happened through a transphyseal mechanism. Contrary to previous studies [9,18,30], we found three patients with an ICP waveform before dissection and after fixation who later developed osteonecrosis. These represent examples of a false-negative test result.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is unclear, however, whether revascularization was related to the integrity of the retinacular vessels or if it may have happened through a transphyseal mechanism. Contrary to previous studies [9,18,30], we found three patients with an ICP waveform before dissection and after fixation who later developed osteonecrosis. These represent examples of a false-negative test result.…”
Section: Discussioncontrasting
confidence: 99%
“…One of the benefits of the subcapital realignment through the surgical dislocation approach (modified Dunn procedure) is visualization and protection of the vascular retinaculum and direct assessment of perfusion of the femoral head during surgery. Femoral head perfusion may be assessed by evaluating bleeding after creating a 2-mm drill hole [9,24,30,31], by laser-Doppler flowmetry [9,30], and/or by intracranial pressure probe monitoring [24]. Assessment of perfusion during surgery may allow for adjustments of positioning the femoral head if blood flow decreases after the femoral head is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…. In K. Ziebarth et al [22] study postoperative Alpha angle ranged from 27 0 to 60 0 with mean of 40.6 0 , in H. HUBER et al [25] study postoperative Alpha angle ranged from 27 0 to 77 0 with mean of 41.4 0 , in T.Slongo et al [24] study postoperative Alpha angle ranged from 24 0 to 53 0 with mean of 38 0 . In Novais et al [26] study postoperative Alpha angle ranged from 40 0 to 51 0 with mean of 44 0 (Table 4).…”
Section: Discussionmentioning
confidence: 96%
“…In K. Ziebarth et al [22] study 23 patients were classified as moderate and 12 patients were severe, in H. HUBER et al [25] study 3 patients were classified as mild, 17 were moderate, and 10 patients were severe, in T.Slongo et al [24] study 6 patients were classified as mild, 8 were moderate, and 9 patients were severe. Novais et al [26] study 15 patients (100%) were severe.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,23 Some short series showed that modified Dunn procedure with femoral neck shortening and femoral head reduction and fixation seems to have a low rate of AVN with a good anatomic result. 32e34 In-situ fixation is considered as the most safe surgical technique regarding vascularization 30,32 but its functional result could be worse because of partial reduction of upper femoral deformity. Preoperative traction is not risky 8,35,36 or has no real benefit.…”
Section: Discussionmentioning
confidence: 99%